Internalisasi Nilai-Nilai Pancasila Melalui Pendekatan CTL (Contextual Teaching Learning) Pada Siswa Kelas 2 SDI Bayanul Azhar Sumbergempol Tulungagung - Anggia Novita Putri; Yudi Krisno Wicaksono (Journal Innovation In Education, 2024)
The changing times allow children to freely access technology anywhere and anytime. However, over time, they did not care about the values of Pancasila, which caused them to behave deviantly and not in accordance with the values of Pancasila. Therefore, SDI Bayanul Azhar, especially grade 2, applies the internalization of Pancasila values when learning Pancasila education in the classroom. Internalization uses an approach, namely the CTL (Contextual Teaching Learning) approach. There are several problem formulations based on the observations of researchers, namely, (1) What is the process of implementing the internalization of Pancasila values with the CTL approach in grade 2 students of SDI Bayanul Azhar?, (2) How is the understanding of grade 2 students of SDI Bayanul Azhar on the value of God in the process of internalizing Pancasila values through the CTL approach?, (3) What are the obstacles of teachers in the process of internalizing Pancasila values through the CTL approach for grade 2 students at SDI Bayanul Azhar? This research uses qualitative methods. Data collection techniques are carried out through observation, interviews, and documentation. The results obtained by the researcher are that most of the grade 2 students of SDI Bayanul Azhar already understand the meaning of divine values, then the implementation of internalization using the CTL approach, which is to associate material with everyday life, for the constraints that exist in the internalization process, which is constrained by time.